The N, N′-dioxide/Ni(ii)-catalyzed asymmetric inverse-electron-demand hetero-Diels–Alder reaction of methyleneindolinones with hetero-substituted alkenes1. Issue 58 (25th July 2015) - Zhou, Yuhang; Lin, Lili; Yin, Chengkai; Wang, Zhengmeng; Liu, Xiaohua; Feng, Xiaoming
<x xml:space="preserve">Abstract</x> The asymmetric inverse-electron-demand hetero-Diels–Alder reaction of methyleneindolinones with hetero-substituted alkenes catalyzed by chiral N, N′-dioxide/Ni(ii) complexes has been accomplished, affording dihydropyran-fused indoles in up to 99% yield, >95 : 5 dr and 99% ee.